Time evolution of the spectrum of the cesium high pressure discharge light source. (January 2015) - Rakic, Mario; Pichler, Goran
Abstract: The time development of the emission spectrum after the ignition of a high pressure cesium lamp has been studied by means of a high resolution digital spectrometer. Many different spectral phenomena of atomic, ionic or molecular origin have been followed in time. Xenon spectral lines were detected only within the first few seconds after the ignition. Cesium resonance lines appear almost immediately with xenon spectral lines. The former have an extraordinarily interesting time evolution, especially in their far quasistatic wings. Recombination continua to 6p and 5d levels appear almost immediately as Cs satellite and other molecular bands. Allowed and forbidden atomic spectral lines follow slightly different time evolutions. All these temporal spectral changes of the high pressure cesium lamp could be used for further improvement of this interesting white light source. Highlights: Time development of the cesium high pressure pulsed discharge lamp spectrum. Observed rise and fall of the xenon lines in first 7 s of plasma burning. Atomic spectral lines and molecular bands observed in emission and in absorption. The satellite bands in the wings of the resonance lines were followed in time.